Which way to emancipation?: race and ethnicity in American socialist thought, 1876-1899 - Costaguta, Lorenzo (2017)
This thesis investigates socialist ideas of race and ethnicity in the US during the Gilded Age. By charting the attempts of the Socialist Labor Party to defend the economic and social rights of racial minorities such as African Americans, Chinese immigrants, and Native Americans, it explores the tension between the struggle for class emancipation on the one hand and the demand for racial equality on the other. Focusing on a group of little-investigated newspaper sources, in many cases involving new translations from German-language local socialist press, this thesis challenges the idea held by many historians of American radicalism that late-nineteenth century socialists were apparently uninterested in race. On the contrary, American socialists of the Gilded Age actively engaged with the specific interracial and inter-ethnic composition of the US working class. Applying both methods of institutional and intellectual history, this thesis argues that the Socialist Labor Party between 1876-1899 was divided into two main areas of opinion: the first, defined in this work as “colour-blind internationalist,” held that class solidarity – rather than race and ethnicity – should be used to unite workers and fight for their rights. The second, here termed “scientific racialist,” used a variety of intellectual approaches, which spanned from pseudo-scientific theories of race to Darwinism and anthropology, to demonstrate the existence of a hierarchy of human groups with different levels of physical, cultural, and social development. From the late 1870s to the end of the 1880s the scientific racialist position was prominent in the Socialist Labor Party, but was contested by colour-blind assertions. Indeed, when Daniel De Leon became the party’s leader in the 1890s, he imposed colour-blind socialism as the sole approach. This moved American socialism away from anti-egalitarian outlooks, but created a blind spot in which socialists stopped recognising race as a key element that shaped the social dynamics of the country – a situation that made it hard for them to successfully implement anti-racist policies. This, in turn, helps to explain the relative historic weakness of socialism in the US.